2018
DOI: 10.14789/jmj.2018.64.jmj18-p31
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Vulnerability and Depression Among Japanese University Athletes

Abstract: In the case of an excessive burden imposed on self, a person with vulnerability he/she perceives unprotected against the load. Vulnerability is defined as"a susceptibility to damage to self, a state that may be fragile or hurt."University athletes may often experience psychological, physical, and social stressors, which may cause vulnerable athletes to exhibit stress responses. Our previous studies of vulnerability among athletes have revealed that women have higher scores than men. Therefore, this study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 4 publications
4
9
0
Order By: Relevance
“…A positive correlation was found between vulnerability and depressive symptoms. Since this result is consistent with previous research ( Hayashi, 2002 ; Yamaguchi et al, 2018 ), we believe that the measure developed in this research reflects the construct of vulnerability. Therefore, if one is vulnerable to something happening in one’s daily life, one may experience more depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A positive correlation was found between vulnerability and depressive symptoms. Since this result is consistent with previous research ( Hayashi, 2002 ; Yamaguchi et al, 2018 ), we believe that the measure developed in this research reflects the construct of vulnerability. Therefore, if one is vulnerable to something happening in one’s daily life, one may experience more depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, Satici et al (2016) revealed a negative relationship between psychological vulnerability and social safety and found social safety to be a significant negative predictor of psychological vulnerability. Additionally, similar to the findings of Yamaguchi et al (2018 , 2019) , who studied the relationship between vulnerability and mental health, Demirci et al (2019) reported that psychological vulnerability is an important factor for mental health and well-being. According to Yelpaze et al (2021) , empirical support for potential factors in the relationship between psychological vulnerability, social connectedness, and well-being is still lacking.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations